PEMANFAATAN INFOGRAFIS BERBASIS ILUSTRASI UNTUK MELESTARIKAN DAN MENDIDIK SISWA SD TANTANG PERMAINAN TRADISIONAL BETAWI - Damba Permatasakti; Afifah Salsabila (Prahasta Publisher (manage by: DRPM Institut Bisnis dan Teknologi Indonesia), 2023)
Most of the traditional games in Jakarta are attached to the Betawi culture. Betawi traditional games not only have cultural values ​​that are implied to be preserved but are helpful for children in practicing their soft skills in real life. However, the game's popularity among the younger generation has decreased significantly because the primary method of disseminating the traditional Betawi game, namely word-of-mouth, has been passed down from generation to generation. This resulted in the inevitable extinction of traditional games. This research was conducted to find new media for preserving traditional Betawi games by adopting the Design Thinking method from IDEO and Stanford d. School: Empathy, Interpretation, Ideas, Experiments, and Tests. The result of this research is an illustrated book with an infographic style intended for elementary school students. The infographic style provides an overview of the equipment required, step-by-step instructions on how to play using short narrations, and displays game situations in vivid scenes. The tasteful design style of elementary school students applying the Betawi color scheme received positive feedback from the target market during testing. Thus, the book proved to arouse elementary school student's interest in learning and playing traditional Betawi games. So that efforts to preserve Betawi traditional games with new media is achieved.